A Semi‐parametric Model for Microstructure Analysis of Advanced High‐strength Dual‐phase Steels Considering Sample Variation. (17th October 2016) - Zhang, Nailong; Yang, Qingyu; Wu, Xin
Abstract : Microstructure analysis of advanced high‐strength dual‐phase steels has attracted increasing attention in recent years, as the microscopic properties of steels significantly affect their material properties and behaviors. As a result, the steel microstructure plays an important role of product quality. However, most of the existing methods only consider a single microstructure sample, while the unit‐to‐unit variability among different samples is ignored. As a result, they cannot be applied for steel quality control. In this study, we propose a semi‐parametric microstructure modeling method that can capture the variation across different microstructure samples. The proposed model can be used for both isotropic materials and anisotropic materials in which the microstructure properties in the vertical direction and those in the horizontal direction are different. The proposed model is applied for both quality control of dual‐phase steels and microstructure reconstruction without having to conduct physical experiments. A case study is conducted by applying the developed methods to advanced high‐strength steels. Copyright © 2016 John Wiley & Sons, Ltd.